The Impact of Using Computer Applications Programs as a Tool in Accounting Education on the Performance of the Students of Financial Accounting Course - Tarawneh, Ahmad Saleem (International Review of Management and Marketing, 2018)
The aim of this study was to identify the impact of using computer applications in accounting education in higher education institutions in Jordan. The study was based on the experimental approach in presenting, analyzing data and drawing forth the results, using a sample of (67) students who were chosen intentionally. The results have showed a statistically significant effect of using computer applications in accounting education on the performance of the students of financial accounting course at Mu’tah University. In the light of the results, some conclusions were drawn, most importantly is that the use of computer technologies and applications is a part of the strategic orientation of education development. Based on the conclusions, the study recommends the need to push for using these techniques in an organized and systematic manner. Keywords: Computer Applications Programs; Accounting Education; Financial Accounting; Performance; Jordan JEL Classification: M41